Kootenaia burkei, a new genus and species of slug from northern Idaho, United States (Gastropoda: Pulmonata: Arionidae) - Leonard, William P.; Chichester, Lyle; Baugh, Jim; Wilke, Thomas (Zootaxa, 2003)
A new genus and species of arionid slug, Kootenaia burkei n. gen. et n. sp., are formally described from northern Idaho, United States. This taxonomic decision is based on comparative anatomical and molecular data involving representatives of a total of ten species and three additional genera (Hemphillia, Prophysaon, and Zacoleus) of the family Arionidae. The anatomical analyses show that the new genus is characterized by a major autapomorphy, the complete absence of an epiphallus, which is found in all other arionids. The molecular analyses using two mitochondrial genes and the anatomical data produce congruent topologies. Overall, there is a high degree of concordance between the anatomical and molecular datasets.